Venezuelan equine encephalitis emergence: Enhanced vector infection from a single amino acid substitution in the envelope glycoprotein - Brault, Aaron C. (National Academy of Sciences, 2004)
In 1993 and 1996, subtype IE Venezuelan equine encephalitis (VEE) virus caused epizootics in the Mexican states of Chiapas and Oaxaca. Previously, only subtype IAB and IC VEE virus strains had been associated with major outbreaks of equine and human disease. The IAB and IC epizootics are believed to emerge via adaptation of enzootic (sylvatic, equine-avirulent) strains for high titer equine viremia that results in efficient infection of mosquito vectors. However, experimental equine infections with subtype IE equine isolates from the Mexican outbreaks demonstrated neuro-virulence but little viremia, inconsistent with typical VEE emergence mechanisms. Therefore, we hypothesized that changes in the mosquito vector host range might have contributed to the Mexican emergence. To test this hypothesis, we evaluated the susceptibility of the most abundant mosquito in the deforested Pacific coastal locations of the VEE outbreaks and a proven epizootic vector, Ochlerotatus taeniorhynchus. The Mexican epizootic equine isolates exhibited significantly greater infectivity compared with closely related enzootic strains, supporting the hypothesis that adaptation to an efficient epizootic vector contributed to disease emergence. Reverse genetic studies implicated a Ser → Asn substitution in the E2 envelope glycoprotein as the major determinant of the increased vector infectivity phenotype. Our findings underscore the capacity of RNA viruses to alter their vector host range through minor genetic changes, resulting in the potential for disease emergence.